Hypoglycemia in cystic fibrosis during an extended oral glucose tolerance test. Issue 12 (16th October 2020) - Armaghanian, Natasha; Hetherington, Julie; Parameswaran, Venkat; Chua, Elizabeth L.; Markovic, Tania P.; Brand‐Miller, Jennie; Steinbeck, Kate
Abstract: Background: Hypoglycemia in cystic fibrosis (CF), in the absence of glucose‐lowering therapies, has long been identified as an important issue in the management of CF. There is currently still no unifying hypothesis for its etiology. Aim: The aims of this study were to perform a 3‐h oral glucose tolerance test (OGTT) in participants with CF and (1) document glucose, insulin, glucagon, glucagon‐like‐peptide‐1 (GLP‐1), and glucose‐dependent insulinotropic peptide (GIP) release patterns within varying glucose tolerance groups during the OGTT; (2) determine the prevalence of hypoglycemia during the OGTT; and (3) define any association between hypoglycemia and patterns of insulin, glucagon, GLP‐1, and GIP release. Methods: Eligible participants attending an adult CF clinic completed a 3‐h OGTT. Hypoglycemia on OGTT was defined as mild (glucose 3.4–3.9 mmol/L), moderate (glucose 3.1–3.3 mmol/L), and severe (glucose ≤ 3 mmol/L). Hormones were measured at fasting, 30, 60, 120, and 180 min. Results: Twenty‐four participants completed the study, of which 7 had normal glucose tolerance, 12 had abnormal glucose tolerance, and 5 had cystic fibrosis related diabetes (CFRD). All participants had a delayed insulin response compared with normative data. All glucose tolerance groups showed appropriate and similar suppression of fasting glucagon. Four participants (17%) had mild hypoglycemia, three (13%) had moderate hypoglycemia, and eight (33%) had severe hypoglycemia. No participant with CFRD demonstrated hypoglycemia. Of the 19 participants without CFRD, 15 (79%) experienced hypoglycemia. Participants with hypoglycemia had greater peak glucose and insulin responses than those that did not have hypoglycemia, and this approached significance ( p = .0625 for glucose and p = .0862 for insulin). No significant mean differences between GLP‐1 and GIP release were found. There was no relationship between hypoglycemia and modulator therapy. Conclusion: Postprandial hypoglycemia was unmasked by the extension of an OGTT to 3 h. Delayed and abnormal insulin release, and ineffective counter‐regulatory action of glucagon may have a role in its etiology.